Impact of epilepsy and its treatment on brain metastasis from solid tumors: A retrospective study - Maschio, Marta; Maialetti, Andrea; Giannarelli, Diana; Koudriavtseva, Tatiana; Galiè, Edvina; Fabi, Alessandra (Frontiers in Neurology, 2022)
Introduction: Retrospective observational study on medical records of patients with epilepsy related brain metastases (BM) to evaluate efficacy, safety and possible interaction with cancer treatment of different anti-seizure medications (ASMs) and the risk of seizures. Materials and Methods: We consecutively reviewed all medical records of epilepsy-related BM patients from 2010 to 2020 who were followed for at least one month at the Brain Tumour-related Epilepsy Center of the IRCCS Regina Elena National Cancer Institute Rome, Italy. Results: We selected 111 cancer patients. Of these, only 42 had at least undergone a second neurological examination. In the whole population, 95 (85.2%) had seizures and 16 patients had no seizures (14.4%). The most frequently first ASM prescribed was LEV (40.5%). We observed a significant correlation between tumour site and probability of having seizures, but not between seizure type and age (>65 or <65 years). Among 42 patients, 26 were administered levetiracetam, followed by oxcarbazepine. Until the last follow-up, 19 never changed the first ASM, maintained the same dosage and remained seizure free. After a median of 7 months, 16 (38.1%) required changes in therapeutic treatment due to inefficacy. At the last follow-up, 24 patients (57.1%) were seizure free. Eighteen patients (42.8%) never achieved freedom from seizures despite had at least 2 therapy changes. Two patients changed ASM due to adverse events and 1 to phenobarbital owing to the interaction with cancer treatment. The mean daily dose of first ASM in all 42 patients was very close to the Defined Daily Dose (DDD). Conclusion: In BM patients seizure incidence could be underestimated; a team evaluation performed by oncologist and neurologist together, could guarantee an accurate taking care of both oncological illness and epilepsy, in this fragile patient population. More than 50% of our patients respond to monotherapy with new generation ASMs. Furthermore we deemed in patients receiving chemotherapy the choice of ASM should consider possible interactions with antitumor therapies, for this reason newer generation ASMs should be the preferred choice. It is necessary to get close to the DDD before considering an ASM ineffective in seizure control.